The role of water in supporting food security: Where we are and where we need to go - Ringler, Claudia; Perez, Nicostrato D.; Xie, Hua (International Food Policy Research Institute, 2021)
Although global annual water availability is largely stable, with small increases as a result of accelerated water cycles under climate change (Oki and Kanae 2006), the demand on water resources has grown substantially over the past 50 years, due to population growth, agricultural and economic growth, and urbanization (WWAP 2016; Bates et al. 2008). This has led to increasing competition across water-using sectors and contributed to severe degradation of water and related ecosystems and biodiversity loss in parts of the globe and, in some cases, outmigration of humans. Higher temperatures, less certain precipitation patterns, as well as shorter, more concentrated rains together with prolonged dry seasons are putting further pressure on available water supplies (Bates et al. 2008; Fishman, Jain, and Kishore 2013; WWAP 2016). All of these developments have put access by farmers to water for food production at risk.